A story of belonging: schooling and the struggle of students of refugee experience to belong. Issue 6 (1st November 2020) - Picton, Fiona; Banfield, Grant
ABSTRACT: Finding a place for oneself at school and a sense of membership with others, is important for all school students and vitally important for students of refugee experience. Developing a sense of belonging at school may assist students to settle in to their new country and to gain some control over their lives. This paper uses student voice to illustrate possible facilitators and impediments to belonging for students of refugee experience. It argues that school belonging is not dependent upon English language learning alone and it recommends that changes be made in mainstream school, to offer a more inclusive, welcoming and social just experience for students of refugee experience. It suggests that the established patterns of culture, structure and practice in mainstream school may no longer provide appropriate responses to meet the needs of students with refugee experience.